DAMPAK KUALITAS LAYANAN DAN KUALITAS PRODUK TERHADAP KEPUASAN PELANGGAN HYPERMART BENCOOLEN MALL BENGKULU - Reni Putriani; Donny Dharmawan (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2020)
The purpose of this study was to analyze the impact of service quality and product quality on customer satisfaction Hypermart Bencoolen Mall Bengkulu. The data used are primary data obtained through filling out a questionnaire with a Likert scale. The sample selection method used is purposive sampling. The results of this study indicate that service quality and product quality have a positive and significant effect on customer satisfaction of PT. Hypermart Bencoolen Mall Bengkulu.